Advances in Porous Perovskites: Synthesis and Electrocatalytic Performance in Fuel Cells and Metal–Air Batteries. Issue 2 (11th February 2020) - Yu, Jie; Ran, Ran; Zhong, Yijun; Zhou, Wei; Ni, Meng; Shao, Zongping
Abstract : With a rising energy demand and anabatic environmental crisis arising from the fast growth in human population and society economics, numerous efforts have been devoted to explore and design plentiful multifunctional materials for meeting high‐efficiency energy transfer processes, which happen in various developed energy conversion and storage systems. As a special kind of multi‐metal oxides, perovskite with attractive physical and chemical properties, is becoming a rapidly rising star on the horizon of high‐performance catalytic materials with substantial research behaviors worldwide. The porous nanostructure in targeted catalysts is favorable to the catalytic activity and thus improves the overall efficiency of these energy‐related installations. In this review paper, recent advances made in the porous perovskite nanostructures for catalyzing several anodic or cathodic reactions in fuel cells and metal–air batteries are comprehensively summarized. Plenty of general preparation methods employed to attain porous perovskite‐type oxides are provided, followed by a further discussion about the influence of various strategies on structures and catalytic properties of the porous perovskites. Furthermore, deep insights gathered in the future development of porous perovskite‐based materials for energy conversion and storage technologies are also provided. Abstract : Perovskite oxides are a class of very promising catalytic materials, with the attractive physical and chemical properties. Porous nanostructure shows many advantages in the field of electrocatalysis. The detailed synthesis strategies, potential application in fuel cells and metal–air batteries, and challenges and prospects of such porous perovskite‐type oxides are comprehensively summarized here.